Aspirin-loaded P(3HO)/P(3HB) blend films: potential materials for biodegradable drug-eluting stents. Issue 3 (1st September 2013) - Boccaccini, Aldo R.; Ching, Kuan Yong; Smith, Caroline; Stolz, Martin; Locke, Ian C.; Basnett, Pooja; Knowles, Jonathan C.; Roy, Ipsita
Abstract : Poly(3-hydroxyoctanoate)/poly(3-hydroxybutyrate), P(3HO)/P(3HB), blend films loaded with aspirin were prepared, and the influence of aspirin loading on the surface properties, mechanical, thermal and degradation properties were investigated. Scanning electron microscopy images revealed that the addition of aspirin introduced a new topography on the surface of the blend films. Aspirin contributed to the increase in the hydrophilic nature of the blend films compared with the unloaded blend films. This was complemented by a considerable increase in the total protein adsorption in the aspirin-loaded blend films. The percentage cell viability was higher in the aspirin-loaded blend films compared with the unloaded blend films. There was a decrease in the tensile strength and the Young's modulus with the addition of the aspirin. However, the percentage elongation at break, a measure of elasticity, was higher in the aspirin-loaded films, indicating an increase in their flexibility compared with the unloaded blend films. There was a decrease in the melting temperature ( T m ), glass transition temperature ( T g ) and the crystallization temperature ( T c ) due to the decrease in the crystallinity of the aspirin-loaded blend films in comparison with the unloaded blend films. Finally, controlled release of aspirin was observed without any burst release, and 96·6% release was achieved within 25 d, ideal for the development of biodegradable drug-eluting stents.